Provision of harm‐reduction services to limit unsafe abortion in Tanzania. Issue 2 (23rd November 2016) - Kahabuka, Catherine; Pembe, Andrea; Meglioli, Alejandra
Abstract: Objective: To investigate the feasibility of providing harm‐reduction services to reduce unsafe abortion in Tanzania. Methods: A cross‐sectional study was conducted among 110 women who received harm‐reduction counseling at a public health center in Dar es Salaam between February 10 and October 10, 2014. Background and clinical information was collected for all women; a subgroup (n=50) undertook a semi‐structured survey that measured the type of services women received, women's perception of the services, and pregnancy outcome. The main study outcomes were attendance at the follow‐up visit, type and quality of information women received on both visits, and misoprostol use for pregnancy termination. Results: Overall, 55 (50.0%) women attended follow‐up services. Misoprostol was used for induced abortion among 54 (98.2%); 38 (70.4%) of these women had obtained contraception at the follow‐up visit. Likelihood of attendance for follow‐up was increased among women who were older than 34 years (odds ratio [OR] 2.2, 95% confidence interval [CI] 0.1–35.8), were married (OR 2.1, 95% CI 0.8–5.7), and had a post‐primary education level (OR 2.0, 95% CI 0.8–5.3). On average, 44 (87.0%) women received all required information at the initial counseling session and none reported major complications that required hospitalization. Conclusion: Harm‐reduction services for unsafe abortion are feasible and acceptable, and could provide an excellent opportunity to fight abortion‐related morbidity and mortality in Tanzania. Abstract : Harm‐reduction services for unsafe abortion are feasible and acceptable, and could provide an excellent opportunity to substantially reduce abortion‐related morbidity and mortality in Tanzania.